1995
DOI: 10.1177/107769909507200412
|View full text |Cite
|
Sign up to set email alerts
|

Pronouncements and Denunciations: An Analysis of State Press Association Ethics Codes from the 1920S

Abstract: In light of the Associated Press Managing Editor's recent revision of its ethics code, the time seems right to examine journalism's original ethics codes, created in the 1920s, to discover what virtues and practices the codes' creators presented as indust y standards. Four situational concerns -the rise of press agents, the fallout from World War 1 propaganda, sensationalism's resurgence, and editorial independencecontributed to a noticeable decline of the public's trust in the press. As a result, the codes co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In addition, Brown (1974) observed that the Canons were an "example of implicit self-analysis" (p. 31). Similarly, in their study of state press association ethics codes from the 1920s, Cronin and McPherson (1995) found that those state codes reflected several concerns among journalists. They included the increasing number of public relations practitioners, the revival of sensationalism, and the independence of newspapers from political and business interests.…”
Section: Historical Contextmentioning
confidence: 95%
“…In addition, Brown (1974) observed that the Canons were an "example of implicit self-analysis" (p. 31). Similarly, in their study of state press association ethics codes from the 1920s, Cronin and McPherson (1995) found that those state codes reflected several concerns among journalists. They included the increasing number of public relations practitioners, the revival of sensationalism, and the independence of newspapers from political and business interests.…”
Section: Historical Contextmentioning
confidence: 95%
“…Increased pay was offered as one solution by the ASNE (ASNE Editors, 1927: 99–101), though we have no evidence that publishers followed through on this solution, and Walsh himself continued his profitable business for another decade. In fact, a major critique of this practice during Walsh’s time was not only the ghostwritten origin of the articles but rather that newspapers were surrendering their independence by yielding editorial space to promotional copy that was produced by non-staff members (Cronin and McPherson, 1995).…”
Section: Ghostwriting: the 1920s Professional Debatementioning
confidence: 99%
“…Such professional introspection had been evident for 20 years previously in the pages of the journalism profession's trade publication, Editor and Publisher, which raised concerns about press accuracy as well as propaganda (Rodgers, 2007). State press association codes of ethics in the 1920s specifically singled out the increase in the number of public relations practitioners as a concern (Cronin and McPherson, 1995). Perhaps because of this concern, two national journalism codes of ethics emerged in the 1920s.…”
Section: Why the 1920smentioning
confidence: 99%